2014
DOI: 10.1186/1472-6890-14-11
|View full text |Cite
|
Sign up to set email alerts
|

DKK-1 in prostate cancer diagnosis and follow up

Abstract: BackgroundDickoppf-1 (DKK-1) is a negative regulator of bone formation with tumorigenic potential. The up-regulation of DKK-1 is an early event in prostate cancer (PCa) development, thus we investigated its role as a marker in the diagnosis and prognosis of PCa.MethodsWe retrospectively enrolled 159 patients who underwent prostate biopsy, either for elevated PSA or suspect digital rectal examination, between 2003 and 2010. During the biopsy, one serum sample was collected from all patients; PSA and DKK-1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Serum sclerostin values increased in prostate cancer patients with bone metastases by about 40% in comparison to a control group of age-adjusted men [43]. DKK-1 values were not different in 159 men who were diagnosed with cancer or cancer free by prostate biopsy [149]. However, patients who developed bone metastases in the follow-up were characterized by reduced DKK-1 values.…”
Section: Bone Markers In Diagnosticsmentioning
confidence: 63%
“…Serum sclerostin values increased in prostate cancer patients with bone metastases by about 40% in comparison to a control group of age-adjusted men [43]. DKK-1 values were not different in 159 men who were diagnosed with cancer or cancer free by prostate biopsy [149]. However, patients who developed bone metastases in the follow-up were characterized by reduced DKK-1 values.…”
Section: Bone Markers In Diagnosticsmentioning
confidence: 63%
“…DKK family members are implicated in various developmental, pathological, and physiological processes ( 16 , 27 ). In prostate cancer, DKK-1 acts as a marker of carcinogenesis, and may provide a novel method of prostate cancer prediction for patients with negative primary biopsy results, who may otherwise progress to bone metastasis ( 28 ). Recent studies have demonstrated that overexpression of DKK-1 may be associated with increased angiogenesis ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of DKK1 expression in prostate cancer cell lines have been investigated in several previous studies (Browne et al, 2016;D'Amelio et al, 2014;Hall, Bafico, Dai, Aaronson, & Keller, 2005;Hall, Daignault, Shah, Pienta, & Keller, 2008;Hall et al, 2010;Li et al, 2008b;Thudi et al, 2011). The expression of DKK-1 regulates Wnt-induced osteoblastic activity in prostate cancer cell lines.…”
Section: Role Of Dkk-1 Proteins In Prostate Cancermentioning
confidence: 99%
“…They reported that DKK‐1 perform worse than prostate‐specific antigen (PSA) in the early diagnosis of prostate cancer, but better than PSA in detecting patients who developed prostate cancer during follow‐up. Thus, the authors concluded that DKK‐1 could be a good predictive marker for prostate cancer development and prognosis of bone metastases (D’Amelio et al, ). Taken together, it seems that DKK1 could be a key inhibitory factor for therapeutic intervention in osteoblastic metastases during prostate cancer.…”
Section: Dkk Family Of Wnt Antagonistsmentioning
confidence: 99%